2016
DOI: 10.1002/anie.201601028
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Conjugate Addition of Benzofuran‐2‐ones to Alkyl 2‐Phthalimidoacrylates: Modeling Structure–Stereoselectivity Relationships with Steric and Electronic Parameters

Abstract: A highly predictive model to correlate the steric and electronic parameters of tertiary amine thiourea catalysts with the stereoselectivity of Michael reactions of 3-substituted benzofuranones and alkyl 2-phthalimidoacrylates is described. As predicted, new 3,5-bis(trifluoromethyl)benzyl- and methyl-substituted tertiary amine thioureas turned out to be highly suitable catalysts for this reaction and enabled the synthesis of enantioenriched α-amino acid derivatives with 1,3-nonadjacent stereogenic centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 79 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…found that benzyl diaminocyclohexane‐based squaramide catalysts without electronic perturbation can also lead to excellent enantioinduction in the reaction of acetylacetone and nitrostyrene . Recently, in the Michael addition of 3‐substituted benzofuranones to alkyl 2‐phthalimidoacrylates, we found that the methyl thiourea catalyst, which has the smallest alkyl substituent, can induce stereoselectivities as high as those of 3,5‐bis(trifluoromethyl)benzyl thiourea . These new findings prompted us to revisit the role of the steric hindrance of bifunctional thioureas/squaramides in the stereocontrol of the Michael addition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…found that benzyl diaminocyclohexane‐based squaramide catalysts without electronic perturbation can also lead to excellent enantioinduction in the reaction of acetylacetone and nitrostyrene . Recently, in the Michael addition of 3‐substituted benzofuranones to alkyl 2‐phthalimidoacrylates, we found that the methyl thiourea catalyst, which has the smallest alkyl substituent, can induce stereoselectivities as high as those of 3,5‐bis(trifluoromethyl)benzyl thiourea . These new findings prompted us to revisit the role of the steric hindrance of bifunctional thioureas/squaramides in the stereocontrol of the Michael addition.…”
Section: Resultsmentioning
confidence: 99%
“…Intensive efforts have been made to elucidate mechanisms in this context by using experimental or computational approaches. However, investigations of the links between the stereoselectivity of a reaction and the performance of the catalyst remain elusive till now, and due to their great potential in guiding the design of new catalysts, they warrant immediate exploration ,. In particular, given that 3,5‐bis(trifluoromethyl)phenyl, 3,5‐bis(trifluoromethyl)benzyl, fluorinated ethyl, benzyl, and methyl groups occur in numerous privileged bifunctional hydrogen‐bonding catalysts (Figure ), the reasons behind these phenomena need more rational explanations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzofurans are naturally widespread molecules which have drawn considerable attention over the last few years due to their extensive physiological and pharmacological properties. They display potent biological activites including antihyperglycemic, analgesic, antiparasitic, antimicrobial, antitumor, kinase inhibitor . In addition, various natural and synthetic benzofuran derivatives, known as effective drugs, are used routinely in the treatment of different diseases (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Using this technique, a polynomial equation that correlates the reaction outcome with the chemical descriptors of a catalyst and/or substrate set can be derived. The resultant mathematical model can be used to extrapolate better catalysts through virtual screening thus improving the reaction performance.…”
mentioning
confidence: 99%